1994
DOI: 10.1152/ajplung.1994.267.1.l39
|View full text |Cite
|
Sign up to set email alerts
|

IL-1ra suppresses endotoxin-induced IL-1 beta and TNF-alpha release from mononuclear phagocytes

Abstract: The proinflammatory effects of lipopolysaccharide (LPS) are modulated in large part through the induction of interleukin-1 beta (IL-1 beta) and tumor necrosis factor-alpha (TNF-alpha) release by mononuclear phagocytes. However, IL-1's target cell effects can be suppressed by IL-1 receptor agonist (IL-1ra). Because mononuclear phagocytes produce and respond to IL-1 via IL-1 receptors, we hypothesized that IL-1ra may also be able to block receptors on IL-1 producer cells and inhibit secondary IL-1-induced IL-1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…3A). The exact mechanism of TNF-␣ suppression is unclear; however, a previous study has shown that IL-1ra suppresses TNF-␣ release from macrophages (22). At 6 h following CLP, IL-1␤ and TNF-␣ levels in liver homogenates were not significantly different from baseline.…”
Section: Clp Induces First Proinflammatory and Then Anti-inflammatorymentioning
confidence: 78%
“…3A). The exact mechanism of TNF-␣ suppression is unclear; however, a previous study has shown that IL-1ra suppresses TNF-␣ release from macrophages (22). At 6 h following CLP, IL-1␤ and TNF-␣ levels in liver homogenates were not significantly different from baseline.…”
Section: Clp Induces First Proinflammatory and Then Anti-inflammatorymentioning
confidence: 78%
“…TNF-® is known to be released into the systemic circulation within the rst few hours after the infusion of bacteria or lipopolysacharide into an experimental animal [16]. IL-1¯, which is also released early after sepsis, interacts closely and acts synergistically with TNF-® [19]. IL-8 is released a few hours later and has signi cant chemotatic effects on the leukocytes in the pulmonary circulation [20,24].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that early proin ammatory cytokines [16], such as TNF-®, IL-1¯, and IL-8, may be also be involved in the early phase of APTE. TNF-® is a cytotoxic and proin ammatory cytokine that mediates apoptosis, cell proliferation, and immunomodulation in many pathological conditions [17,18], while IL-1¯acts similarly and causes increase in the vascular permeability of the lung following a wide variety of injuries [19]. The CXC chemokine interleukin-8 (IL-8) is an important activator and chemoattractant for neutrophils and has been implicated in many in ammatory diseases [20][21][22].…”
mentioning
confidence: 99%
“…Thus, there is evidence that the production of IL-1/3 at 2 h was mainly mediated by TNF(~. In contrast, neutralization of endogenous IL-lra had no effects on TNFc~ activity, which means that the production of TNFo~ is not mediated by IL-1 in LPSarthritis, although IL-1 does induce TNF~ in vitro [39,40].…”
Section: Inflamm Resmentioning
confidence: 99%